2021
DOI: 10.1159/000517293
|View full text |Cite
|
Sign up to set email alerts
|

The Paracingulate Sulcus Is a Unique Feature of the Medial Frontal Cortex Shared by Great Apes and Humans

Abstract: Primate brains display a wide range of variation in size and cerebral gyrification, leading to the appearance of novel sulci in particular groups of species. We investigated sulcal organization in the medial frontal cortex of great apes, with a particular focus on the paracingulate sulcus (PCGS). Until recently, the presence of the PCGS was thought to be a structural feature unique to the human brain. However, upon closer examination, the PCGS has been observed as a variable feature that also may appear in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In primates, this abstract ability to be able to deal with symbolic representations of language and thus display complex cognitive processes led to a host of detailed investigations both of behavior and of the structure and function of the primate brain (Maestripieri, 1999;Reader and Laland, 2002). Such investigations and comparative studies between primates and humans continue to this day and have clarified differences (Palomero-Gallagher and Zilles, 2019) and similarities (Miller et al, 2021) between the brain of apes and the human brain. The discoveries of mental time travel (conceiving of past, present, and future) conveyed in sign language added depth to the view that apes are cognitively very advanced, can readily cope with abstract concepts, and imbue gestures with meaning (Leavens, 2004;Liebal and Call, 2012;Fröhlich and Hobaiter, 2018;Hobaiter et al, 2022).…”
Section: Backgroundmentioning
confidence: 99%
“…In primates, this abstract ability to be able to deal with symbolic representations of language and thus display complex cognitive processes led to a host of detailed investigations both of behavior and of the structure and function of the primate brain (Maestripieri, 1999;Reader and Laland, 2002). Such investigations and comparative studies between primates and humans continue to this day and have clarified differences (Palomero-Gallagher and Zilles, 2019) and similarities (Miller et al, 2021) between the brain of apes and the human brain. The discoveries of mental time travel (conceiving of past, present, and future) conveyed in sign language added depth to the view that apes are cognitively very advanced, can readily cope with abstract concepts, and imbue gestures with meaning (Leavens, 2004;Liebal and Call, 2012;Fröhlich and Hobaiter, 2018;Hobaiter et al, 2022).…”
Section: Backgroundmentioning
confidence: 99%
“…Such studies have revealed that although the sulcal patterning of primary sensory cortices more or less resembles one another 20 across species, this relationship is far less consistent in association cortices. For example, while the sulcal organization of visual association cortex was comparable between every human and non-human hominoid hemisphere examined in previous work 15 , the incidence of sulci in medial 14,16,17 and lateral 38 prefrontal cortex, as well as orbitofrontal cortex 64 was substantially different across species. Adding to the complexity, within each of these regions, differences in sulcal incidence rates were greater for some sulci compared to others -elucidating specific areas of cortex that are particularly expanded/more complex in humans.…”
Section: Discussionmentioning
confidence: 75%
“…A fundamental question in comparative biology and systems neuroscience is: What features of the brain are unique to humans? Key insights regarding what features of the brain are unique to humans have been gleaned from studies comparing anatomical and functional features of the human brain to features from the brains of our close evolutionary relative, the chimpanzee [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Of all the features to study, researchers particularly focus on the folds of the cerebral cortex, or sulci, as they generally track with evolutionary complexity 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In sum, fundamental aspects of emotional traits and of psychopathology are controlled in humans by conserved systems including diffuse ascending components that terminate throughout the neocortex (Dubois, Galdi, Han, Paul, & Adolphs, 2018;Dubois et al, 2020). This allows non-humans, from fish through primates, to provide meaningful models (with true homologies) of the core emotion production systems through which the complex sensory filters of more recently evolved cortical systems (Falcone et al, 2020;Miller, Hof, Sherwood, & Hopkins, 2021) change affect, behaviour, cognition, and desire. Both between and within species, trait aspects of these systems depend on genes and their interaction with the developmental environment of the organism.…”
Section: Conservation Of Brain Systemsmentioning
confidence: 99%